Optimisation of culture conditions and characterisation of cutinase produced by recombinant Saccharomyces cerevisiae - Calado, Cecília (2020)
The optimum culture dissolved oxygen concentration and culture pH for the production of cutinase from Fusarium solani pisi by the recombinant Saccharomyces cerevisiae SU50 strain was investigated. Dissolved oxygen concentrations in the fermentation culture of 5, 30 and 60% of air saturation were evaluated. A high cutinase production, specific cutinase activity and the highest cutinase yield on biomass and the highest specific cutinase production rate were obtained with a 5% of air saturation, which could have impact on process economics. Furthermore, at a low dissolved oxygen concentration, the specific growth rate, specific cutinase production rate, cutinase yield on biomass, cutinase activity and specific cutinase activity were increased when the pH control was changed from 5.25 to 6.25. The cutinase, accumulated in the yeast culture presents two glycosilated isoforms with molecular weights of 22.8 and 24.9 kDa measured by SDS-PAGE. Furthermore, cutinase in clarified culture samples presents a linear relationship between estereolytic and lypolitic activity and a high stability at room temperature.